2016
DOI: 10.1111/vde.12398
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureuspenetrate the interkeratinocyte spaces created by skin‐infiltrating neutrophils in a mouse model of impetigo

Abstract: Background-Impetigo is a bacterial skin disease characterized by intraepidermal neutrophilic pustules. Previous studies have demonstrated that exfoliative toxin producing staphylococci are isolated in the cutaneous lesions of human and canine impetigo. However, the mechanisms of intraepidermal splitting in impetigo remain poorly understood. Objective-To determine how staphylococci penetrate the living epidermis and create intraepidermal pustules in vivo using a mouse model of impetigo. Methods-Three Staphyloco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…To address this issue, we recently established a mouse model of bullous impetigo [72]. S. aureus harboring etb gene was inoculated epicutaneously to murine inner pinnae after the stratum corneum was partially removed by tape stripping.…”
Section: How Et-producing S Aureus Penetrate the Epidermis Through Fmentioning
confidence: 99%
“…To address this issue, we recently established a mouse model of bullous impetigo [72]. S. aureus harboring etb gene was inoculated epicutaneously to murine inner pinnae after the stratum corneum was partially removed by tape stripping.…”
Section: How Et-producing S Aureus Penetrate the Epidermis Through Fmentioning
confidence: 99%
“…In this model [ 49 ], there was no intraepidermal or sub-corneal pustules nor the migration of neutrophils, which is inconsistent with the picture for human impetigo. Similar studies [ 50 , 51 ] that used this model and followed the same procedure have reported contrasting results. One study [ 50 ] claimed the formation of intraepidermal pustules resembling human impetigo through epicutaneous inoculation of S. aureus on the inner pinna of the mice.…”
Section: Introductionmentioning
confidence: 93%
“…Human impetigo initially develops as a small vesicle after minor injuries or cuts on the skin, such as abrasions and skin scratches resulting from eczematous lesions or insect bites, rapidly progressing into pustular lesion, and subsequently evolving into an erosion covered by a thick crust [ 8 , 60 , 61 , 62 ]. Other authors [ 45 , 46 , 49 , 50 , 63 ] also suggest that the application of topical inoculation of organisms to the surface of slightly damaged or traumatized skin is likely to more closely resemble the natural route of transmission for GAS and S. aureus . Minor skin traumas perforate the stratum corneum, causing a temporary breach in the integrity of the skin barrier system that enables the inoculated bacteria to permeate or penetrate the epidermis with little hindrance [ 62 , 64 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations